Can Procalcitonin in Cerebrospinal Fluid be a Diagnostic Tool for Meningitis?. Issue 3 (5th May 2014) - Konstantinidis, Theocharis; Cassimos, Dimitrios; Gioka, Theodora; Tsigalou, Christina; Parasidis, Theodoros; Alexandropoulou, Ioanna; Nikolaidis, Christos; Kampouromiti, Georgia; Constantinidis, Theodoros; Chatzimichael, Athanasios; Panopoulou, Maria
<x xml:space="preserve">Abstract</x> Background To study the levels of procalcitonin (PCT) in patients with meningitis and control group and compare them with established markers of infection—such as C‐reactive protein (CRP), high‐sensitivity CRP, and WBC—in cerebrospinal fluid (CSF) and assess the possible discriminative role of PCT in the differential diagnosis of meningitis from other noninfectious diseases. Methods We studied CSF samples of patients from Intensive Care Unit, Internal Medicine, Neurology, Hematology, and Pediatric departments. The total number of patients included in the study was 58. The samples were divided into three groups: group 1 with bacterial meningitis (BM) central nervous system (n = 19); group 2 with viral meningitis (VM, n = 11); and group 3, control group, with noninfectious diseases (n = 28). Results Values of PCT levels >0.5 ng/ml were considered as abnormal. In group 1, mean PCT levels were 4.714 ± 1.59 ng/ml. In group 2, all patients had PCT <0.5 ng/ml (0.1327 ± 0.03 ng/ml). In group 3, the mean PCT levels were <0.1 ng/ml. Conclusion PCT values in CSF can be very helpful in distinguishing BM from VM and other noninfectious diseases.